2000
DOI: 10.1017/s0033291799008879
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive vulnerability in patients with bipolar disorder

Abstract: This study suggests that cognitive vulnerability in patients with bipolar disorder is similar to that described in unipolar disorders. It is not clear whether this dysfunction is a cause or an effect of repeated episodes of bipolar disorder. However, the findings may have implications for clinical treatment as well as suggesting a number of important new avenues of research into psychological models of affective disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
212
4
5

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 251 publications
(242 citation statements)
references
References 18 publications
21
212
4
5
Order By: Relevance
“…A number of studies by different research groups have shown OGM in adults with clinical depression (Brewin, Watson, McCarthy, Hyman, & Dayson, 1998;Goddard, Dritschel, & Burton, 1996;Kuyken & Dalgleish, 1995;Puffet, Jehin-Marchot, Timsit-Berthier, & Timsit, 1991;Wessel, Meeren, Peeters, Arntz, & Merckelbach, 2001), adolescents with major depressive disorder (Park, Goodyer, & Teasdale, 2002) and women with postnatal depression (Croll & Bryant, 2000), as well as in currently euthymic individuals with past major depressive or bipolar episodes (Mackinger, Pachinger, Leibetseder, & Fartacek, 2000;Scott, Stanton, Garland, & Ferrier, 2000) and in sub-clinically dysphoric participants (Goddard, Dritschel, & Burton, 1997;Ramponi, Barnard, & Nimmo-smith, 2004). This combination of findings suggests that OGM could be both a trait and a state marker of depression.…”
Section: Overgeneral Autobiographical Memorymentioning
confidence: 99%
“…A number of studies by different research groups have shown OGM in adults with clinical depression (Brewin, Watson, McCarthy, Hyman, & Dayson, 1998;Goddard, Dritschel, & Burton, 1996;Kuyken & Dalgleish, 1995;Puffet, Jehin-Marchot, Timsit-Berthier, & Timsit, 1991;Wessel, Meeren, Peeters, Arntz, & Merckelbach, 2001), adolescents with major depressive disorder (Park, Goodyer, & Teasdale, 2002) and women with postnatal depression (Croll & Bryant, 2000), as well as in currently euthymic individuals with past major depressive or bipolar episodes (Mackinger, Pachinger, Leibetseder, & Fartacek, 2000;Scott, Stanton, Garland, & Ferrier, 2000) and in sub-clinically dysphoric participants (Goddard, Dritschel, & Burton, 1997;Ramponi, Barnard, & Nimmo-smith, 2004). This combination of findings suggests that OGM could be both a trait and a state marker of depression.…”
Section: Overgeneral Autobiographical Memorymentioning
confidence: 99%
“…A substantial number of studies have now confirmed that many patients with BD have cognitive impairment that persists into the euthymic state. [154][155][156][157][158][159] Impairment has been demonstrated in sustained attention, 160 working memory and executive function, 155 global cognitive functioning, 154 visuospatial recognition memory, 161 problem-solving strategies, 156 declarative memory, 157 and cognitive processing speed. 162 The fact that such impairment is detectable independent of clinical state is suggestive of a trait marker, but factors such as the neuropsychological deterioration secondary to acute episodes of illness, medication treatment, and/or withdrawal effects, long-term effects of comorbid conditions such as substance abuse, or the effect of unrecognized neurobiological changes such as dysregulation of the hypothalamic-pituitary-adrenal (HPA) axis could all contribute to performance deficits in the euthymic state.…”
Section: Cognitive Endophenotypesmentioning
confidence: 99%
“…Manic patients showed impairments on planning and reaction time (RT) (Murphy et al, 1999). During remission, cognitive deficits may persist (van Gorp et al, 1998;Ferrier et al, 1999;Rubinsztein et al, 2000;Scott et al, 2000); euthymic BD patients showed impairments on visuospatial recognition, verbal and nonverbal memory and learning, retrieval of information from semantic memory an increased RT on a planning task (Coffman et al, 1990;Ferrier et al, 1999;Rubinsztein et al, 2000). The fact that cognitive deficits persist during remission suggests that they constitute a trait marker in BD.…”
Section: Introductionmentioning
confidence: 99%